Functional expression of a pseudohypoaldosteronism type I mutated epithelial Na(+) channel lacking the pore-forming region of its α subunit - Bonny, Olivier (American Society for Clinical Investigation, 1999)
The autosomal recessive form of type I pseudohypoaldosteronism (PHA-I) is an inherited salt-losing syndrome resulting from diminution-of-function mutations in the 3 subunits of the epithelial Na(+) channel (ENaC). A PHA-I stop mutation (α(R508stop)) of the ENaC α subunit is predicted to lack the second transmembrane domain and the intracellular COOH-terminus, regions of the protein involved in pore function. Nonetheless, we observed a measurable Na(+) current in Xenopus laevis oocytes that coexpress the β and γ subunits with the truncated α subunit. The mutant α was coassembled with β and γ subunits and was present at the cell surface at a lower density, consistent with the lower Na(+) current seen in oocytes with the truncated α subunit. The single-channel Na(+) conductance for the mutant channel was only slightly decreased, and the appearance of the macroscopic currents was delayed by 48 hours with respect to wild-type. Our data suggest novel roles for the α subunit in the assembly and targeting of an active channel to the cell surface, and suggest that channel pores consisting of only the β and γ subunits can provide significant residual activity. This activity may be sufficient to explain the absence of a severe pulmonary phenotype in patients with PHA-I.